Providing sodium information on a restaurant menu: a case study from the restaurant at Kellogg Ranch part I. Issue 4 (4th July 2019) - Kapoor, Sandra; De Villa-Lopez, Belinda
ABSTRACT: Excess sodium intake is a major risk factor for hypertension, and subsequently, heart disease and stroke, the first and fifth leading causes of death in the United States. For many people, blood pressure rises progressively as salt (sodium chloride) intake increases. The purpose of this study was to determine whether providing sodium information to restaurant guests would influence their menu choices. The sodium study was conducted in a hospitality management college's student operated restaurant. The restaurant was open to the public for lunch and dinner. Once guests were seated, they were given a menu. Guests were given menus for 3 weeks during lunch and dinner without sodium information printed on the menus and for 3 weeks during lunch and dinner with sodium information printed on the menus. The number of orders for each item on both the lunch and dinner menus was recorded during the 3 weeks for lunch and dinner when no sodium information was printed on the menus and during the 3 weeks for lunch and dinner when sodium information was printed on the menus. Each item on the menu was rated as either high in sodium or low in sodium. Statistical analysis was performed on the data collected. Analysis was conducted between lunch and dinner menus with sodium listed and without sodium listed, and between menu items high in sodium and low in sodium. A two-way chi-square test was used to calculate the data. The results showed that whether sodium was listed on the lunch menu or not listed on the lunch menu, guests ordered high sodium menu items. Likewise, the results showed that whether sodium was listed on the dinner menu or not listed on the dinner menu, guests ordered low sodium menu items.